2011
DOI: 10.4061/2011/439518
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Langerhans Cell Histiocytosis on Fine Needle Aspiration Cytology: A Case Report and Review of the Cytology Literature

Abstract: A case of multifocal Langerhans cell histiocytosis in a two-year-old child is presented where fine needle aspiration was helpful in achieving a rapid and accurate diagnosis in an appropriate clinical and radiological setting. This can avoid unnecessary biopsy and guide the management especially where access to histopathology is limited. The highly characteristic common and rare cytological features are highlighted with focus on differential diagnoses and causes of pitfalls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 28 publications
0
52
1
1
Order By: Relevance
“…These three conditions are believed to represent different expressions of the same disorder, now known as LCH. [1]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These three conditions are believed to represent different expressions of the same disorder, now known as LCH. [1]…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation may be induced by a viral infection, a defect in T-cell macrophage interaction and/or a cytokine driven process mediated by tumor necrosis factor, interleukin 11 and leukemia inhibitory factor 1. [1]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, a recent case report by Kumar et al suggests that fine-needle aspiration cytology may also be effective in diagnosing LCH, alleviating the need for an invasive biopsy. 8 Lung involvement in LCH has a variable appearance on chest CT scans, ranging from small peribronchiolar nodular opacities to multiple irregularly-shaped cysts. 1 In the current case, the CT findings were pathognomonic, showing cysts of variable size in both lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Akhtar et al have reported that the degree of eosinophilic infiltrate in cytology specimens varies from scant to abundant in different areas of LCH lesions and also in different organs. However, presence of eosinophils or Charcot-Leyden crystals is a subtle feature that should alert the pathologist to include LCH in the differential diagnosis [26,27]. Onsite adequacy assessment with procurement of extra material for ancillary studies is helpful in clinching the diagnosis of this rare entity in thyroid FNA specimens.…”
Section: Fine Needle Aspiration and Biopsymentioning
confidence: 99%